Prevention of Mental Health Disorder among Adolescents during The COVID-19 Pandemic - Khariri, Aqidah; Arya Ivan Mahendra; Maesarah; Nadhira Rahma Augustria; Rayhan Alma Shafannisa Heru; Zulfa Zahra (Jurnal Psikiatri Surabaya, 2022)
Introduction: The COVID-19 pandemic has negative impacts on mental health and is commonly found in adolescence. Mental health disorders, such as anxiety and depression, can increase the risk of many physical health problems and reduce performance in the work and social environments as well. Several studies about COVID-19 and anxiety showed that the younger population (especially young adults) tended to have more anxiety. When compared to the older population, the younger population also uses social media more often which can cause anxiety due to information overload and misinformation. Objective: This literature review is aimed to discuss further and broaden insight into the importance of mental health awareness and efforts to prevent mental health disorders among teenagers during the COVID-19 pandemic. Methods: Conduncting previous studies from PubMed and Google Scholar using these following keyword (mental health) AND (anxiety) AND (depression) AND (covid 19) AND (adolescents) by the journal publication filter for the last ten years. Results: Mental health promotions intend to increase an individual's mental capacity, overcome difficulties, and encourage someone to seek the necessary health help if they feel mental health disorder. It also promotes the prevention of stigma against mental disorders. In the COVID-19 pandemic. Conclusions: Understanding the symptoms and prevention of mental health disorders such as health promotion and protection from specific mental illnesses are becoming the primary prevention of mental health problems.